HOW THE LITERARY PERSPECTIVE OF THE PROPHET IS REVEALED IN THE MODERN NOVELS HABIBURRAHMAN EL SHIRAZY AND AHMAD FUADI (BAGAIMANA PERSPEKTIF SASTRA NABI DIUNGKAPAKAN DALAM NOVEL MODERN HABIBURRAHMAN EL SHIRAZY DAN AHMAD FUADI) - Emil Septia; Wahyudi Rahmat; Samsiarni Samsiarni; Yulia Sri Hartati (Universitas PGRI Sumatera Barat, 2023)
Prophetic is imitating the actions of the Prophet. Muslims should strike a balance between learning about their religion and the modern world, so studies of the prophets might become research material. They should work together to solve the issues confronting an Allah-inspired society. However, as contemporary science advances, religious science is abandoned, and humankind moves further away from ethical principles, humanization, transcendence, and liberty. Following what Muhammad taught as a prophet and the Messenger of Allah, creating prophetic science courses is an important matter to be addressed to merge the abundance of human knowledge with revelation. This research aimed to characterize the prophetic in the works of Habiburrahman El Shirazy and Ahmad Fuadi. Qualitative research methods were used for this study. In this study, content analysis was the methodology of choice. The information was presented as descriptions of the prophetic in the story in the form of words, sentences, and speeches. Kembara Rindu, Ayat-ayat Cinta 2 by Habiburrahman, El Shirazy, and Ahmad Fuadi's Menara 5: Negeri were the three books used for the research. According to the findings, the prophetic humanization sub-indicators connecting fraternity, mutual respect, responsibility, and caring may be noticed in those three novels. Helping the wrong people and being willing to make sacrifices are discovered to be indicators of the liberation prophecy. In contrast, the prophetic transcendence includes markers (prayer, dhikr, and prayer) of human dependence on God, affirms an absolute difference between God and humanity, and attributes recognition of God's absolute rules to human reason.